Therapy for locomotor apparatus diseases: Efficiency and safety - N. V. Chichasova (Современная ревматология, 2015)
The paper reviews the literature on the treatment of chronic diseases of the locomotor apparatus. In arthrological diseases, pain is most commonly chronic and has a different genesis, mainly inflammatory, as well as mechanical, vascular, neurogenic, and psychosomatic, which requires continuous, at times long-term, therapy to improve quality of life in patients. Requirements for long-term drug therapy that can reduce the degree of inflammation and pain are determined by the magnitude of the analgesic and anti-inflammatory effect and safety of drugs. Mostly elderly age, the presence of comorbidities, and the need for attendant treatment complicate anti-inflammatory and analgesic therapy in these patients. It is shown that the representative of a class of selective cyclooxygenase-2 inhibitors meloxicam is as effective as classical nonsteroidal anti-inflammatory drugs (NSAIDs), but it is much well tolerated by elderly patients in particular. There is information on the efficacy and safety of meloxicam, as evidenced by researches and real clinical practice. The paper shows the higher safety of meloxicam having an efficacy equal to that of nonselective NSAIDs, its low frequency of gastrointestinal complications, which is comparable with that of celecoxib, and no cardiotoxicity. It also gives clinical and experimental findings suggesting that meloxicam has no negative effect on the cartilage.